Reflections on Physics Education and Communication with Tibetan Monastics - Beck, Judith; Burton, Justin C.; Kamela, Martin; Kuchera, Michelle P.; Lovell, Amy J.; Nordstrom, Kerstin; Tenzin, Thinley; Ziffer, Julie (Frontiers in Communication, 2021)
Physics education research, a field that is now over 100 years old, has made it clear: the key to teaching physics successfully is to prioritize getting the concepts across, and the mathematical representation (``laws") can come later. On the other hand, conceptual representations are steeped in culture and language, while the corresponding ``laws" are universal. The ETSI program provided a unique opportunity to re-imagine conceptual physics for Tibetan monastic culture. This perspective describes the major challenges derived from this experience over multiple areas of physics, and addresses two central questions: 1) How does the translation and interpretation of key terms such as energy, motion, charge, and system change the connotations surrounding physical laws? 2) What are the practical strengths and weaknesses of teaching conceptual physics using well-developed methods in the USA, and what can educators learn about the emergence of understanding?